Psychological aspects of living with inflammatory bowel diseases - Hobot, Maciej; Strzałkowska, Paulina; Grabski, Wojciech; Kosiński, Maciej; Szaj, Dominika; Raczkowska, Michalina; Szymajda, Wiktor; Trojańska, Aleksandra; Kaźmierczak, Monika (Quality in Sport, 2025)
Inflammatory bowel diseases (IBD), encompassing Crohn’s disease and ulcerative colitis, are chronic, relapsing conditions that significantly impact not only patients’ physical health but also their psychological well-being. The disease course, characterized by alternating periods of remission and exacerbation, is associated with pain, diarrhea, fatigue, and the need for constant adaptation to fluctuating health status. Patients frequently experience depression, anxiety disorders, chronic stress, reduced self-esteem, and body image disturbances, particularly following surgical interventions. The disease exerts a profound influence on social, occupational, and family life, often resulting in isolation and stigmatization. This work underscores the importance of psychological support, including cognitive-behavioral therapy (CBT), acceptance and commitment therapy (ACT), and mindfulness-based interventions, all of which facilitate patients’ adaptation to living with a chronic illness. The integration of psychological care with medical treatment, the development of psychoeducational programs, and stigma-reduction initiatives are strongly recommended. A comprehensive approach that addresses both somatic and psychological dimensions is essential to improve the quality of life in patients with IBD. Further research is warranted to better understand the most effective psychological support strategies and their impact on disease outcomes.